"O estar hemiplégico": o processo de luto simbólico do corpo em pessoas hemiplégicas por acidente vascular cerebral - Maso, Julia Schmidt (2009)
The objective of this study is to understand and describe the difficulties of a person with hemiplegia as a consequence of a CVA (Cerebrovascular Accident), commonly known as stroke, and the process of symbolic grief of the body and the sequels. The emotional repercussion due to physical limitations acts significantly on the social, economical and emotional scope of the individual, causing disorganization to his/her life. To face these changes, the person has to count on his/her internal and external resources, which will or will not enable the elaboration of the process of the symbolic grief. A qualitative study was carried out based on the Theory of Attachment by John Bowlby with the participation of four hemiplegic adult patients. The data collection included a semi-oriented interview to describe and analyze the significance of the interrelation of himeplegia, between the body representation and the subjectivity of each person. The information arisen from qualitative analysis procedures was discussed and the conclusion was that it is difficult to measure, validate and recognize the existence of losses caused by the disease and the gradual appropriation of reality. The physical rehabilitation aiming at independence is evaluated according to the gain in life quality of the participants. However, mechanisms of defense, as denial or non acceptance, demonstrate the difficulty to adapt to a new reality. According to the results, we conclude that it is important to identify the expectations of the handicapped person, the significance he/she attributed to the disease and to his/her himeplegia. This survey supports the need to investigate the repercussion of the CVA in general to obtain a better result from the rehabilitation process